Efficacy of exercise-based interventions in preventing falls among community-dwelling older persons with cognitive impairment: is there enough evidence? An updated systematic review and meta-analysis. (11th June 2021) - Li, Fuzhong; Harmer, Peter; Eckstrom, Elizabeth; Ainsworth, Barbara E; Fitzgerald, Kathleen; Voit, Jan; Chou, Li-Shan; Welker, Fei Li; Needham, Shana
Abstract: Objective: Exercise prevents falls in the general older population, but evidence is inconclusive for older adults living with cognitive impairment. We performed an updated systematic review and meta-analysis to assess the potential effectiveness of interventions for reducing falls in older persons with cognitive impairment. Methods: PubMed, EMBASE, CINAHL, Scopus, CENTRAL and PEDro were searched from inception to 10 November 2020. We included randomised controlled trials (RCTs) that evaluated the effects of physical training compared to a control condition (usual care, waitlist, education, placebo control) on reducing falls among community-dwelling older adults with cognitive impairment (i.e. any stage of Alzheimer's disease and related dementias, mild cognitive impairment). Results: We identified and meta-analysed nine studies, published between 2013 and 2020, that included 12 comparisons (N = 1, 411; mean age = 78 years; 56% women). Overall, in comparison to control, interventions produced a statistically significant reduction of approximately 30% in the rate of falls (incidence rate ratio = 0.70; 95% CI, 0.52-0.95). There was significant between-trial heterogeneity (I 2 = 74%), with most trials (n = 6 studies [eight comparisons]) showing no reductions on fall rates. Subgroup analyses showed no differences in the fall rates by trial-level characteristics. Exercise-based interventions had no impact on reducing the number of fallers (relative risk = 1.01; 95% CI, 0.90–1.14). Concerns about risk of bias in these RCTs were noted, and the quality of evidence was rated as low. Conclusions: The positive statistical findings on reducing fall rate in this meta-analysis were driven by a few studies. Therefore, current evidence is insufficient to inform evidence-based recommendations or treatment decisions for clinical practice. PROSPERO Registration number: CRD42020202094.